The COVID-19 pandemic: an unprecedented tragedy in the battle against childhood obesity - Storz, Maximilian Andreas (Clinical and experimental pediatrics, 2020)
The childhood obesity pandemic has emerged as an important public health problem in many countries. Obese children are likely to become obese adults, and adult obesity is associated with an increased risk of morbidity. Therefore, controlling the childhood obesity epidemic has become a top public health priority worldwide. The current coronavirus disease 2019 (COVID-19) pandemic may significantly impede this important mission and constitute an unprecedented tragedy in the global battle against childhood obesity. This manuscript presents evidence that the COVID-19 pandemic will aggravate the childhood obesity epidemic and lead to significant weight gain in school children by creating an unprecedented obesogenic environment. Within the last few months, many countries took uncompromising measures in response to the COVID-19 pandemic, including school closures and quarantine. While these steps are often necessary to ensure infection control, they may have a significant negative effect on children's mental and physical health. Physical, nutritional, and psychosocial factors that promote obesity in children during this special situation complementarily contribute to an unprecedented obesogenic environment. Large-scale quarantine and home confinement will impose new and unfamiliar stressors on children, thereby worsening the childhood obesity epidemic. Most importantly, adverse childhood events resulting from a predicted increase in domestic violence within the next few months will significantly contribute to this concern. The scenario presented in this review is of paramount public health importance and must be considered during future pandemic planning. Involved stakeholders, including governments, schools, and families, must make all possible efforts to minimize the impact of the COVID-19 epidemic on childhood obesity.